(untitled) (Human Factors in Design, 2022)
With the growing use of bicycles in cities, the market has been expanding its products and services to better serve its users. However, some details still do not provide due attention and may be a future problem. One of them is the saddle, which aims to support the cyclist’s weight on the sitting bones, providing support for the body to accommodate the bicycle and, as it is in direct contact with the pelvic region, it can cause several problems, especially in terms of vaginal health. For this reason, an assessment of the usability of saddles was carried out under the users’ perception in order to identify gaps to be filled and the best ones to be resolved to guarantee the safety, quality and health of cyclists.